Calcination Temperature Effect on Characteristic Properties of Na2/3[Fe1/2Mn1/2]O2 Synthesized by Sol-Gel Reaction - Diah Agustina Puspitasari; Supriyono Supriyono; Christina Wahyu Kartikowati; Mar’atul Fauziyah; Femiana Gapsari; Vania Mitha Pratiwi; Devina Annora H Br Butar-Butar; Ira Marisa D.N; Rashieka Putri Maghfiroh; Yudha Bhakti Prasetia; Rivanda Adi I. R; Irginata Aqil H; Roihan Rajabi; Umar Khalid Zaki Abdul (Program studi Teknik Kimia UNS, 2024)
Abstract. Recently, Na2/3[Fe1/2Mn1/2]O2 has received attention as a potential candidate material for cathode sodium-ion batteries. However, this material was synthesized by a solid-state process, resulting in larger particle size and nonuniform morphology. The larger particle size will sluggish the Na ion diffusion. Here we report the synthesis of Na2/3[Fe1/2Mn1/2]O2 using a simple sol-gel process. The X-ray diffraction revealed that the sample was identified as Na2/3[Fe1/2Mn1/2]O2 with a hexagonal crystal structure. However, the impurities are formed at diffraction angles of 36.28°, 45.03°, and 51.23°. Calcination temperature affects the formation of the crystal phase, grain growth, morphology, and particle size. Our findings provide valuable insight into the development of Na2/3[Fe1/2Mn1/2]O2 material with desirable properties. Keywords:Sol-Gel, Solid State, Grain Growth, Calcination, Na2/3[Fe1/2Mn1/2]O2